A randomized controlled trial of 7-day intensive and standard weekly cognitive therapy for PTSD and emotion-focused supportive therapy. - Ehlers, A; Hackmann, A; Grey, N; Wild, J; Liness, S; Albert, I; Deale, A; Stott, R; Clark, D (American Psychiatric Association, 2014)
OBJECTIVE: Psychological treatments for posttraumatic stress disorder (PTSD) are usually delivered once or twice a week over several months. It is unclear whether they can be successfully delivered over a shorter period of time. This clinical trial had two goals: to investigate the acceptability and efficacy of a 7-day intensive version of cognitive therapy for PTSD and to investigate whether cognitive therapy has specific treatment effects by comparing intensive and standard weekly cognitive therapy with an equally credible alternative treatment. METHOD: Patients with chronic PTSD (N=121) were randomly allocated to 7-day intensive cognitive therapy for PTSD, 3 months of standard weekly cognitive therapy, 3 months of weekly emotion-focused supportive therapy, or a 14-week waiting list condition. The primary outcomes were change in PTSD symptoms and diagnosis as measured by independent assessor ratings and self-report. The secondary outcomes were change in disability, anxiety, depression, and quality of life. Evaluations were conducted at the baseline assessment and at 6 and 14 weeks (the posttreatment/wait assessment). For groups receiving treatment, evaluations were also conducted at 3 weeks and follow-up assessments at 27 and 40 weeks after randomization. All analyses were intent-to-treat. RESULTS: At the posttreatment/wait assessment, 73% of the intensive cognitive therapy group, 77% of the standard cognitive therapy group, 43% of the supportive therapy group, and 7% of the waiting list group had recovered from PTSD. All treatments were well tolerated and were superior to waiting list on nearly all outcome measures; no difference was observed between supportive therapy and waiting list on quality of life. For primary outcomes, disability, and general anxiety, intensive and standard cognitive therapy were superior to supportive therapy. Intensive cognitive therapy achieved faster symptom reduction and comparable overall outcomes to standard cognitive therapy. CONCLUSIONS: Cognitive therapy for PTSD delivered intensively over little more than a week was as effective as cognitive therapy delivered over 3 months. Both had specific effects and were superior to supportive therapy. Intensive cognitive therapy for PTSD is a feasible and promising alternative to traditional weekly treatment.